Study the structure of Hg1-x Cdx Te alloy (Baghdad Science Journal, 2025)
A study carried out to prepare Hg1-xCdxTe compound and to see the effect on increasing the percentage of x on the compound structure by using x-ray diffraction and atomic absorption for 0